2018
DOI: 10.2139/ssrn.3214757
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Exchange Rate Dynamics on Agricultural Output Performance in Nigeria

Abstract: The study investigated the possible asymmetric effect of real exchange rate dynamics on agricultural output performance in Nigeria over the period of 1981 to 2016 by collecting data from secondary sources. The study employed a combination of stationary and nonstationary variables as was found out through the ADF unit root test. Based on the Bounds test for cointegration, a long-run relationship was absent between real exchange rate and agricultural output, irrespective of specifications. Generally, the result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…This relationship implies that an appreciation in exchange rates have a positive effect on the growth of earnings from agriculture. This finding corroborate the study conducted by (Adekunle & Ndukwe, 2018) who found an evidence of exchange rate affecting the share of agriculture in gross domestic product positively. However, the finding contradicts with the study of (Muraya, 2014;Adongo, John, Zeph & Muyima 2020) who obtained a negative influence of exchange rate on Kenya's agricultural output.…”
Section: Discussion and Analysis Of Ecm Resultssupporting
confidence: 92%
“…This relationship implies that an appreciation in exchange rates have a positive effect on the growth of earnings from agriculture. This finding corroborate the study conducted by (Adekunle & Ndukwe, 2018) who found an evidence of exchange rate affecting the share of agriculture in gross domestic product positively. However, the finding contradicts with the study of (Muraya, 2014;Adongo, John, Zeph & Muyima 2020) who obtained a negative influence of exchange rate on Kenya's agricultural output.…”
Section: Discussion and Analysis Of Ecm Resultssupporting
confidence: 92%
“…Second, like the conventional ARDL, it also affords the opportunity of evaluating the existence of a long-run relationship among variables, also called the bounds test. Finally, NARDL offers a framework which permits the evaluation of dynamic effects of both negative and positive changes in the regressors on a specific dependent variable (Adekunle and Ndukwe 2018).…”
Section: Empirical Methodologymentioning
confidence: 99%
“…In the case of Thailand, changes in macroeconomic factors such as exchange rate improved the agricultural sector performance. Likewise, Adekunle and Ndukwe (2018) observed that changes in exchange rate, interest rate and other macroeconomic factors have considerable impact on Thailand 's agricultural sector. However, the downward trend of agricultural sector revealed can be ascribed to the influences of some of these macroeconomic factors.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%